1987
DOI: 10.1159/000226447
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Epirubicin in Combination Chemotherapy of Advanced Ovarian Cancer

Abstract: The therapeutic efficacy of the combination of cyclophosphamide + epirubicin + cisplatin was evaluated in 107 previously treated or untreated patients with advanced ovarian cancer. The overall response rate was 58.8%, complete remission 36.4% (mean duration 7.62 months) and partial remission 22.4% (mean duration – 6.74 months). The response was rated in function of age, menopausal status, performance status and previous therapy. Toxicity (in case of 109 patients) was evaluated according to the WHO recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The response rate was related to age, menopausal status, and performance status. Eckhardt et al (185) concluded that their preliminary results with epirubicin indicated efficacy similar to that of doxorubicin but with less toxic side effects, and especially less cardiotoxicity. In another 4 studies (181,(186)(187)(188) doxorubicin was replaced by epirubicin in the AP regimen.…”
Section: Phases Zi Trials Combinationsmentioning
confidence: 99%
“…The response rate was related to age, menopausal status, and performance status. Eckhardt et al (185) concluded that their preliminary results with epirubicin indicated efficacy similar to that of doxorubicin but with less toxic side effects, and especially less cardiotoxicity. In another 4 studies (181,(186)(187)(188) doxorubicin was replaced by epirubicin in the AP regimen.…”
Section: Phases Zi Trials Combinationsmentioning
confidence: 99%
“…Cytotoxic combinations including platinum are the most efficacious schedules in treating advanced ovar ian cancer [4], Our study compared the carboplatin-PE regimen, which was expected to exhibit only few side effects [6,8], with the conventional PAC schedule [5], At the dosages we used, the two-drug schedule was generally well tolerated but showed less antineoplastic activity, as reflected by relapse-free rates, than the standard PAC regimen. Since the initial results with the PE combination were disappointing, we discon tinued this protocol.…”
Section: Discussionmentioning
confidence: 99%
“…How ever, carboplatin has been reported to be considerably more myelotoxic, producing mainly leukopenia and thrombocytopenia [6,7]. Epirubicin, an anthracycline derivative, has a therapeutic index similar to that of Adriamycin but in some studies has been shown to be lass cardiotoxic [8,9], In the present study the combination of carboplatin and epirubicin (PE) was used in the treatment of advanced ovarian cancer.…”
Section: Introductionmentioning
confidence: 90%